War Stories in Post-Conflict Society: The Experience of The Kayeli Christian Refugees in Ambon - Pattiserlihun, Selvone Christin; Ahnaf, Mohamad Iqbal; Narciso, Jerson Benia (Pascasarjana IAIN Pontianak, 2024)
Conflict narratives that develop in post-conflict societies are always considered dangerous as conflict triggers that lead to new conflicts. In communities where oral tradition is the primary source of knowledge, storytelling about past contests becomes a central means of transmitting both violent and peaceful cultures. Post-conflict society cannot be separated from the role of war stories in forming individuals and constructing dynamics of communal relations. This study aims to observe and analyze the extent of the role and influence of conflict-telling in post-conflict societies, particularly in conflict-vulnerable communities that were victims of the 1999 conflict in Maluku. This qualitative research was conducted in 2023. The data was collected through in-depth interviews with 15 Kayeli Refugee respondents, who were selected as a sample of vulnerable people based on objective scientific considerations. The results of this study indicate that conflict-vulnerable communities still maintain war stories up to 20 years after the conflict, both with nuances of violence and peace in the limited public and domestic space of religious segregation that is not reached by peacebuilders in efforts to peacebuilding in Ambon. Interestingly, conflict experiences, especially violent stories, become a tool to maintain segregation and present the continuation of structural and cultural violence. On the other hand, there are stories of peace and reflection on the conflict that can be used as a new way to support simple peacebuilding in Ambon as the Multicultural Capital of Maluku.